VD_FINDINFO Arrêt / 2015 / 417 vom 19. Juni 2015 - VD Tribunal cantonal (2015)
NOUVELLE DEMANDE, MESURE D'INSTRUCTIONASSURANCE SOCIALE, INCAPACITÉ DE TRAVAIL, REVENU D'INVALIDE | 17 LAI, 28 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 87 RAI